Visuospatial Performance in Patients with Statistically-Defined Mild Cognitive Impairment - Wasserman, Victor (J Clin Exp Neuropsychol, 2020)
BACKGROUND AND OBJECTIVE: The Oblique Effect denotes superior performance for perceiving horizontal or vertical rather than diagonal or oblique stimuli (Appelle, 1972). The current research investigated the Oblique Effect in patients with mild cognitive impairment (MCI). RESEARCH DESIGN AND METHODS: Four statistically-determined groups were studied; patients with little to no cognitive impairment (non-MCI); subtle cognitive impairment (SCI); amnestic MCI (aMCI); and a combined mixed/dysexecutive MCI (mixed/dys MCI). The Oblique Effect was measured with the Judgment of Line Orientation Test (JOLO). Comprehensive neuropsychological assessment was also obtained. Between-group differences for JOLO oblique and non-oblique test stimuli were analyzed. Hierarchical linear regression models were constructed to identify relations between accuracy for oblique and non-oblique test items and neurocognitive domains. RESULTS: The mixed/dys MCI group demonstrated lower accuracy for oblique test items compared to non-MCI patients. Accurate responding to oblique test items was associated with better performance on tests measuring executive control, processing speed, naming/lexical retrieval, and verbal concept formation. No between-group differences were seen for non-oblique items and these items were not associated with cognition. DISCUSSION AND IMPLICATIONS: Significant impairment on oblique test items distinguished patients with multi-domain/dysexecutive MCI from non-MCI patients. Accurate responding to oblique test items was associated with a complex array of neuropsychological tests suggesting that multidimensional neuropsychological skills underlie the visuospatial reasoning abilities necessary for successful oblique line identification. Research associating the Oblique Effect with additional test paradigms and MRI-defined neuroanatomical regions in MCI may provide more information about the brain-behavior relations that underlie MCI subtypes.